Design of Lookup-Table (LUT) Decoder for Protograph-Based Low-Density Parity-Check (LDPC) codes - Duangthong, Chatuporn; Phakphisut, Watid (My University, 2022)
The Belief-propagation (BP) algorithm is a powerful decoder for LDPC codes. However, the BP algorithm requires the high complexity of the check node operation. Therefore, in the previous works, a lookup table (LUT)-based decoder has been proposed for LDPC codes. In this work, we propose the LUT design for protograph LDPC codes. Our LUT design can support the parallel edge, variable node with degree-1 and punctured variable node. As a result, the coding losses of 2-, 3-and 4-bit quantization of LUT decoder are 1.6, 0.5 and 0.1 dB compared to BP algorithm.
Keywords: channel quantizer; LUT-based decoder; protograph density evolution; protograph LDPC code